Centralized Diagnostics of Ignition System - Okrouhly, M.; Novak, J. (Elektronika ir Elektrotechnika, 2014)
Current trends in the passenger car industry are focused on reduction of manufacturing costs and thus increasing competitiveness on the automotive market. This paper introduces a new approach to vehicle diagnostics, promising direct cost reduction of in-vehicle diagnostic subsystems. The new approach provides for an easy transition from currently used concept of decentralized diagnostic probes to a centralized concept, based on (in an ideal case) a single diagnostic probe. This concept is demonstrated in a case study, which is focused on vehicle ignition system diagnostics. Diagnostic signatures are measured in vehicle supply network, and classified using additional information acquired from internal vehicle communication network. Case study results are presented including the discussion of advantages and limits of the centralized diagnostics concept. DOI: http://dx.doi.org/10.5755/j01.eee.20.10.5666